Tonight on the Titanic - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1999)
The magic tree house transports Jack and Annie to the deck of the Titanic to find a mysterious gift that will free a small dog from a magic spell.
"A Stepping Stone book."
RL: 2.2.
006-009.
340
Accelerated Reader AR
Keywords: Titanic (Steamship) -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Survival after airplane accidents, shipwrecks, etc. -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction